Proceso de atención de enfermería en paciente de 26 años con anemia hemolítica autoinmune - Estrada Gómez, Willian Humberto (2021)
Hemolytic anemia occurs when the bone marrow is no longer producing enough red blood cells to make up for those that are being destroyed. The present clinical case concerns a 26-year-old male patient with a diagnosis of autoimmune hemolytic anemia, a history of HIV diagnosed more than 10 years ago in addition to pulmonary tuberculosis of more than 2 years ago without proper treatment, admitted to the Hospital general "Dr. Liborio Panchana Sotomayor" with a clinical picture of more than 1 month ago with a decline in his general condition, agitation, he refers to weight loss more than two months ago, tests are carried out. Through the assessment by Maryori Gordo functional patterns, it was possible to determine the altered patterns, which together with the taxonomies NANDA, NOC, NIC, allowed to determine the nursing actions, improving the clinical manifestations in a favorable way.